2000
DOI: 10.1086/315298
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoproliferative Responses to Recombinant HIV‐1 Envelope Antigens in Neonates and Infants Receiving gp120 Vaccines

Abstract: Children of mothers infected with human immunodeficiency virus type 1 (HIV-1) were immunized at birth and at 1, 3, and 5 months with 1 of 3 doses of recombinant gp120 vaccines prepared from SF-2 or MN strains of HIV-1. A total of 126 children were not infected; 21 received adjuvant only. Vaccine recipients developed lymphoproliferative responses on >/=2 occasions, responding more often to homologous HIV-1 antigens than did adjuvant recipients (56% vs. 14%; P<.001). Responses were appreciated after 2 immunizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 15 publications
2
37
0
Order By: Relevance
“…We demonstrated that both vaccines, MVA-SIVgpe and SIVmac1A11, elicited rapid immune responses in infant macaques. Thus, the immune system of newborn monkeys is competent to make immune responses, a finding in agreement with the results of HIV-1 vaccine trials in human neonates (4,26). Neither of the two vaccines in our study prevented SIV-infection after oral challenge at 4 weeks of age.…”
Section: Discussionsupporting
confidence: 91%
“…We demonstrated that both vaccines, MVA-SIVgpe and SIVmac1A11, elicited rapid immune responses in infant macaques. Thus, the immune system of newborn monkeys is competent to make immune responses, a finding in agreement with the results of HIV-1 vaccine trials in human neonates (4,26). Neither of the two vaccines in our study prevented SIV-infection after oral challenge at 4 weeks of age.…”
Section: Discussionsupporting
confidence: 91%
“…A neonatal HIV-1 vaccine that rapidly induces systemic and mucosal protective immunity would therefore represent a major advance. A variety of HIV-1 vaccine candidates have been studied with adults, but very few studies of HIV-1 vaccines have been performed in neonates (2,8,23,25,26,37,38,40). Considering the unique features of the neonatal immune system and the need to induce mucosal immune responses rapidly to protect newborns from breast milk HIV-1 transmission, it is important to investigate the immunogenicity of candidate HIV-1 vaccines directly in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…First, neonates have immature immune systems, and it is unclear whether vaccine vectors that are immunogenic in adults will be comparably immunogenic in neonates. Very few studies of HIV-1 or simian immunodeficiency virus (SIV) vaccines have been performed with neonatal rhesus monkeys (23,37,38,40) and humans (8,25,26). Moreover, heterologous prime-boost regimens that have been studied with adult rhesus monkeys (5,7,22) typically require 6 months or longer to induce peak immune responses, and such timing would not be optimal for a pediatric HIV-1 vaccine.…”
mentioning
confidence: 99%
“…Infants were immunized with 4 vaccine doses between 0 and 20 weeks of age. Both vaccines were shown to be safe and to induce humoral and cellular immune responses (64,65). In the initial phase of the study, infants were immunized with escalating doses of vaccines to identify an "optimal vaccine dose" (63).…”
Section: Hiv Vaccine Responses In Infants and Adultsmentioning
confidence: 99%
“…In the initial phase of the study, infants were immunized with escalating doses of vaccines to identify an "optimal vaccine dose" (63). Interestingly, infants who received the lowest vaccine dose had a higher frequency of T cell lymphoproliferative responses than infants immunized with higher vaccine doses (65), suggesting that low vaccine doses may be required in early life. HIV vaccine safety in infants was also demonstrated in PACTG 326 (66).…”
Section: Hiv Vaccine Responses In Infants and Adultsmentioning
confidence: 99%